Impact of the Macmillan specialist Care at Home service: a mixed methods evaluation across six sites - Johnston, Bridget; Patterson, Anne; Bird, Lydia; Wilson, Eleanor; Almack, Kathryn; Mathews, Gillian; Seymour, Jane (BioMed Central, 2018)
Background: The Midhurst Macmillan Specialist Palliative Care at Home Service was founded in 2006 to improve community-based palliative care provision. Principal components include; early referral; home-based clinical interventions; close partnership working; and flexible teamwork. Following a successful introduction, the model was implemented in six further sites across England. This article reports a mixed methods evaluation of the implementation across these ‘Innovation Centres’. The evaluation aimed to assess the process and impact on staff, patients and carers of providing Macmillan Specialist Care at Home services across the six sites. Methods: The study was set within a Realist Evaluation framework and used a longitudinal, mixed methods research design. Data collection over 15 months (2014–2016) included: Quantitative outcome measures – Palliative Performance Scale [PPS] and Palliative Prognostic Index [PPI] (n= 2711); Integrated Palliative Outcome Scales [IPOS] (n= 1157); Carers Support Needs Assessment Tool [CSNAT] (n= 241); Views of Informal Carers–Evaluation of Services[VOICES-SF] (n= 102); a custom-designed Service Data Tool [SDT] that gathered prospective data from each site (n= 88). Qualitative data methods included: focus groups with project team and staff (n=32groups with n= 190 participants), and, volunteers (n= 6 groups with n = 32 participants). Quantitative data were analysed using SPPS Vs. 21 and qualitative data was examined via thematic analysis. Results: Comparison of findings across the six sites revealed the impact of their unique configurations on outcomes,compounded by variations in stage and mode of implementation. PPS, PPI and IPOS data revealed disparity in early referral criteria, complicated by contrasting interpretations of palliative care. The qualitative analysis, CSNAT and VOICES-SF data confirmed the value of the Macmillan model of care but up take of specialist home-based clinical interventions was limited. The Macmillan brand engendered patient and carer confidence, bringing added value to existing services. Significant findings included better co-ordination of palliative care through project management and a single referral point and multi-disciplinary teamwork including leadership from consultants in palliative medicine, the role of health care assistants in rapid referral, and volunteer support. Conclusions: Macmillan Specialist Care at Home increases patient choice about place of death and enhances the quality of end of life experience. Clarification of key components is advocated to aid consistency of implementation across different sites and support future evaluative work.